Super wear-resistant diamond composite material and preparation method thereof
By using a specific ratio of multi-alloy and modified porous carbon for sintering in diamond composites, the problem of mismatch between carcass and diamond wear is solved, the grinding performance and service life are improved, and the thermal conductivity is improved.
Patent Information
- Application Number
- CN202411732213.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The wear of the carcass and diamond materials during the wear process does not match the diamond, which affects the grinding efficiency and service life.
Multi-alloys, diamonds, modified porous carbons and adhesives are mixed at a specific mass ratio and then sintered to form an ultra-wear-resistant diamond composite material. Among them, the multi-alloy consists of Fe, Co, Ni, Cu, W and Sn, and the modified porous carbon is modified by intercalation treatment and polydopamine modification.
It improves the grinding performance and service life of the composite material, and at the same time improves the thermal conductivity, ensuring matching wear between the carcass and diamonds.
Smart Images

Figure CN119553159A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of diamond composite materials, and in particular to a super wear-resistant diamond composite material and a preparation method thereof. Background Art
[0002] Diamond is the hardest substance naturally existing in nature. It also has the advantages of good wear resistance, high thermal conductivity, good electrical insulation and strong corrosion resistance. It is widely used in cutting, grinding, drilling and the electronics industry. Diamond composite superhard abrasives, such as grinding heads and grinding discs, are playing an increasingly important role in high-end chip processing, ceramics and other fields. With the increasing demand for machining accuracy, machining efficiency and service life of abrasives, the quality of existing diamond abrasives is becoming increasingly difficult to meet the increasing demand.
[0003] Metal bond diamond material is the most widely used, applied and used type at present. It has the characteristics of high matrix strength, hardness and wear resistance, but it also has the disadvantages of poor self-sharpening and mismatch between matrix and diamond wear. There are some methods to coat the metal bond and the diamond body to improve the overall performance. For example, CN118241075A discloses a wear-resistant multi-element alloy-diamond composite material and its preparation method, which is to coat the surface of the diamond with a metallized layer and then coat it with a multi-element alloy Cu 35 Ni 20 Cr 15 Fe 20 After the Co5W3Ti2 is mixed, it is sintered in two stages and then placed in a boron trichloride atmosphere for further sintering. The presence of the metallization layer reduces the thermal damage and graphitization of the diamond, and the wear-resistant metal boride is formed by calcination in the boron trichloride, thereby improving the strength and wear resistance of the diamond composite material. CN114921677A discloses a high self-sharpening and strong heat dissipation high entropy alloy-diamond superhard composite material and its preparation method and application, inorganic particles, high entropy alloy powder and diamond abrasive grains are added to an organic binder to obtain a semi-solid raw material; the semi-solid raw material is squeezed into a mold or formed by a roller pressing and cutting process to obtain a composite material green body; the composite material green body is placed in a sintering device for sintering to obtain an internally porous high entropy alloy-diamond superhard composite material.
[0004] At present, the improvement method of metal bond diamond material is mainly to improve the overall performance by increasing the strength of the metal bond. However, this method may cause the wear of the matrix and the diamond to be mismatched, which not only affects the grinding efficiency but also may reduce the service life. It is necessary to provide a metal-diamond composite material with good matching. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a super wear-resistant diamond composite material, which is obtained by mixing multi-element alloy, diamond, modified porous carbon and adhesive in a mass ratio of 90-100: 3-5: 0.5-1: 0.5-2 and then sintering;
[0006] Among them, the multi-element alloy is Fe 15~30 Co 10~15 Ni 10~15 Cu 30~50 W 2~5 Sn 5~10 .
[0007] The multi-element alloy components of the present invention are mainly composed of Fe, Co, Ni and Cu, supplemented by W and Sn. Among them, Fe has good wettability to carbide-forming elements, good wettability to diamond, good sintering performance, and can react with the diamond surface to generate Fe3C, thereby increasing the holding power of diamond. Co also has good sintering performance at a relatively low temperature, and the matrix structure after sintering presents a fine grid, is not prone to hardening, and has good self-sharpening properties of the matrix. Ni does not produce carbides on the diamond surface, but can spread on the diamond surface, has a large adhesion work, and can increase the holding power of diamond. The adhesion work of Ni is larger than that of Co and smaller than that of Fe. The main function of Ni is to react with Cu to increase the strength of the matrix, react with low-melting-point substances, and reduce the loss of low-melting-point substances. Cu has good compatibility with most metal elements and good sintering performance. Although Cu has poor wettability to diamond, large wetting angle, and low holding ability to diamond, adding other elements to form alloys with Cu can improve Cu's wetting to diamond and reduce the wetting angle, thereby increasing the holding force. W is a carbide-forming element and can be used as a skeleton material. W has good compatibility with other bonding metals and is well wetted by metals such as Cu, Co, Ni, and Fe. Sn has a low melting point, which can improve the holding force of the matrix on diamond and reduce the wetting angle between the matrix and diamond. Moreover, tin can form solid solutions with many elements, which can reduce the melting point of the alloy and improve the pressing formability.
[0008] There have been reports on the use of graphene and carbon nanotubes in diamond composite materials. Porous carbon is also a carbon material, and also has the advantages of good thermal conductivity, high stability, good mechanical properties, and high specific surface area. At the same time, the preparation method is simpler. The use of organic acid metal salts, such as citrate metal salts, gluconate metal salts, gallate metal salts, amino acid metal salts, etc. to prepare carbon materials has also been reported. Organic acid metal salts can be used as self-templates and carbon sources. Under high temperature calcination under protective gas, organic components are carbonized, inorganic components are in situ decomposed and carbonized products are etched, and porous carbon with rich pores can be prepared after removing inorganic impurities.
[0009] In order to further improve the surface properties of porous carbon prepared by organic acid metal salts, the porous carbon was intercalated with fatty amines to expand its interlayer spacing. Subsequently, a layer of polydopamine was modified on the surface of the porous carbon by self-polymerization of dopamine to further enhance the interaction between the porous carbon and the multi-element alloy during sintering.
[0010] Furthermore, the preparation method of the modified porous carbon comprises:
[0011] The organic acid metal salt is placed in a protective atmosphere and calcined to obtain porous carbon;
[0012] The porous carbon, aliphatic amine and ethanol aqueous solution are mixed and then subjected to ultrasonic treatment to obtain intercalated porous carbon;
[0013] The intercalated porous carbon, dopamine hydrochloride and ethanol aqueous solution are mixed, the pH is adjusted, and then stirred for reaction to obtain modified porous carbon.
[0014] In the present invention, the type of the organic acid metal salt does not need to be strictly limited, and illustratively it can be at least one of zinc citrate, sodium gluconate, potassium tartrate, sodium L-aspartate, and the like.
[0015] Furthermore, the mass ratio of the porous carbon, the fatty amine, and the ethanol aqueous solution is 2-5:1-3:20-30;
[0016] The ultrasonic treatment lasts for 3 to 8 hours at a power of 100 to 200 W and a frequency of 20 to 50 kHz;
[0017] The mass ratio of the intercalated porous carbon, dopamine hydrochloride and ethanol aqueous solution is 2-5:1-3:60-80;
[0018] Adjust pH to 8.5-9.5.
[0019] The concentration of the ethanol aqueous solution used in the present invention does not need to be strictly limited, and can be 20 wt % to 80 wt % by way of example. The type of the soluble molybdenum salt does not need to be strictly limited, and can be at least one of ammonium molybdate, sodium molybdate, and the like by way of example.
[0020] Although the intercalation and polydopamine modification enhance the dispersion performance of the modified porous carbon in the dispersed multi-element alloy, and improve the grinding performance of the diamond composite material, the modified porous carbon is mainly attached to the diamond surface, which reduces the improvement of the porous carbon on the expansion coefficient and thermal conductivity of the composite material. Because friction and grinding will generate a lot of heat, especially in the absence of coolant, the heat dissipation and expansion coefficient of the binder are particularly important. Abrasive tools with high thermal conductivity can quickly conduct the heat generated by friction and grinding. In order to improve the performance of porous carbon, a certain amount of molybdenum is also chelated on the surface of polydopamine to promote the dispersion of the modified porous carbon during sintering, further improving the comprehensive performance of the composite material.
[0021] Furthermore, after the intercalated porous carbon, dopamine hydrochloride and ethanol aqueous solution are stirred, a soluble molybdenum salt in an amount of 0.2 to 0.5 times the mass of the intercalated porous carbon is added.
[0022] Furthermore, the fatty amine has 4 to 20 carbon atoms.
[0023] Furthermore, the particle size of the multi-component alloy is 50 to 200 μm.
[0024] Furthermore, the diamond has a particle size of 100 to 300 μm.
[0025] Furthermore, the adhesive includes at least one of paraffin, polyvinyl alcohol, and stearic acid.
[0026] The present invention also provides a method for preparing a super wear-resistant diamond composite material, comprising:
[0027] The Fe powder, Co powder, Ni powder, Cu powder, W powder and Sn powder are mixed and sintered to obtain the multi-element alloy Fe 15~30 Co 10~15 Ni 10~ 15 Cu 30~50 W 2~5 Sn 5~10 ;
[0028] The multi-element alloy, diamond, modified porous carbon and adhesive are mixed in a mass ratio of 90-100:3-5:0.5-1:0.5-2 and then sintered to obtain a super wear-resistant diamond composite material.
[0029] Furthermore, the sintering is performed by spark plasma sintering at a temperature of 800 to 1000° C. and a pressure of 20 to 30 MPa for 5 to 15 minutes.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The present invention optimizes the proportion of each component in the multi-component alloy, and improves the sintering performance and the holding force of the matrix on diamond by introducing Sn with a low melting point. The modified porous carbon is well dispersed in the multi-component alloy, which improves the overall strength, significantly improves the grinding performance and service life of the composite material, and at the same time improves the thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A flow chart showing a method for preparing the super wear-resistant diamond composite material of the present invention is shown;
[0033] Figure 2 The scanning electron microscope image of the multi-element alloy and diamond at the fracture of the abrasive tool sample of Comparative Example 4 is shown;
[0034] Figure 3 The scanning electron microscope image of the multi-element alloy and diamond at the fracture of the abrasive tool sample of Example 1 is shown;
[0035] Figure 4 The scanning electron microscope image of the multi-element alloy and diamond at the fracture of the abrasive tool sample of Example 2 is shown;
[0036] Figure 5 The scanning electron microscope image of the multi-element alloy and diamond at the fracture of the abrasive tool sample of Comparative Example 1 is shown;
[0037] Figure 6 The scanning electron microscope image of the multi-element alloy and diamond at the fracture of the abrasive tool sample of Comparative Example 3 is shown. DETAILED DESCRIPTION
[0038] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0039] Some of the raw materials used in the examples and comparative examples of the present invention are described as follows:
[0040] The particle size of Fe powder, Co powder, Ni powder, Cu powder, W powder and Sn powder are all 50μm, and the purity is greater than 99.99%, which are customized by Youyan New Materials Co., Ltd.
[0041] Diamond, model D60, with a particle size of 150-200 μm, was purchased from Henan Bolairong Superhard Materials Co., Ltd.
[0042] Other raw materials not mentioned are common raw materials. The above content is only to help illustrate the present invention and shall not be construed as a strict limitation of the present invention. Those skilled in the art can directly purchase the same / similar raw materials from the market or prepare them by themselves. These contents will not be repeated in the examples.
[0043] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Example 1
[0045] like Figure 1As shown, a method for preparing a super wear-resistant diamond composite material comprises the following steps:
[0046] S1. Preparation of multi-element alloy powder: Fe powder, Co powder, Ni powder, Cu powder, W powder and Sn powder were weighed in a molar ratio of 25:12:13:40:4:6, put into a graphite mold, and sintered by spark plasma at a temperature of 900°C and a pressure of 25 MPa for 10 min to obtain a multi-element alloy block; the alloy block was made into Fe with a particle size of 150 μm by gas atomization method. 25 Co 12 Ni 13 Cu 40 W4Sn6 multi-element alloy powder;
[0047] S2. Preparation of composite materials: Mix multi-element alloy powder, diamond, modified porous carbon and paraffin in a mass ratio of 100:4:0.6:1 and put into a graphite mold. Use spark plasma sintering at a temperature of 850°C and a pressure of 30 MPa for 15 minutes to obtain an ultra-wear-resistant diamond composite material.
[0048] The method for preparing the modified porous carbon comprises:
[0049] T1. Place zinc citrate in a tubular furnace in a nitrogen atmosphere, heat it to 700°C at a heating rate of 3°C / min and keep it warm for 2 hours. After the heating is completed, cool it naturally and collect it to obtain a black solid. Immerse the black solid in 2 mol / L hydrochloric acid to remove inorganic impurities, wash it with water and ethanol three times each, filter it, and transfer it to a 120°C constant temperature oven to dry it for 12 hours to obtain porous carbon;
[0050] T2, after the porous carbon, octylamine and 60wt% ethanol aqueous solution were stirred and mixed at a mass ratio of 3:1:25 at a speed of 350rpm, ultrasonicated at an ultrasonic power of 150W and a frequency of 30kHz for 5h, washed with water and ethanol three times each, filtered and transferred to a constant temperature oven at 120℃ for drying for 12h to obtain intercalated porous carbon;
[0051] T3. The intercalated porous carbon, dopamine hydrochloride and 60 wt% ethanol aqueous solution were stirred and mixed at a mass ratio of 3:1:75 at 500 rpm for 5 min, and then the pH was adjusted to 9.3 with 10 wt% ammonia water and stirred for 12 h. After washing with water and ethanol three times each, the mixture was filtered and transferred to a constant temperature oven at 120°C for drying for 12 h to obtain modified porous carbon.
[0052] Example 2
[0053] A method for preparing a super wear-resistant diamond composite material, comprising the following steps:
[0054] S1. Preparation of multi-element alloy powder: Fe powder, Co powder, Ni powder, Cu powder, W powder and Sn powder were weighed in a molar ratio of 25:12:13:40:4:6, put into a graphite mold, and sintered by spark plasma at a temperature of 900°C and a pressure of 25 MPa for 10 min to obtain a multi-element alloy block; the alloy block was made into Fe with a particle size of 150 μm by gas atomization method. 25 Co 12 Ni 13 Cu 40 W4Sn6 multi-element alloy powder;
[0055] S2. Preparation of composite materials: Mix multi-element alloy powder, diamond, modified porous carbon and paraffin in a mass ratio of 100:4:0.6:1 and put into a graphite mold. Use spark plasma sintering at a temperature of 850°C and a pressure of 30 MPa for 15 minutes to obtain an ultra-wear-resistant diamond composite material.
[0056] Wherein, the preparation method of modified porous carbon is:
[0057] T1. Place zinc citrate in a tubular furnace in a nitrogen atmosphere, heat it to 700°C at a heating rate of 3°C / min and keep it warm for 2 hours. After the heating is completed, cool it naturally and collect it to obtain a black solid. Immerse the black solid in 2 mol / L hydrochloric acid to remove inorganic impurities, wash it with water and ethanol three times each, filter it, and transfer it to a 120°C constant temperature oven to dry it for 12 hours to obtain porous carbon;
[0058] T2, after the porous carbon, octylamine and 60wt% ethanol aqueous solution were stirred and mixed at a mass ratio of 3:1:25 at a speed of 350rpm, ultrasonicated at an ultrasonic power of 150W and a frequency of 30kHz for 5h, washed with water and ethanol three times each, filtered and transferred to a constant temperature oven at 120℃ for drying for 12h to obtain intercalated porous carbon;
[0059] T3. The intercalated porous carbon, dopamine hydrochloride, and 60 wt% ethanol aqueous solution were stirred and mixed at a mass ratio of 3:1:75 at 500 rpm for 5 min, and then 0.3 times the mass of the intercalated porous carbon was added with ammonium molybdate tetrahydrate, and then the pH was adjusted to 9.3 with 10 wt% ammonia water, and the stirring was maintained. The reaction was carried out for 12 h. After the reaction was completed, the mixture was washed with water and ethanol three times each, filtered, and transferred to a constant temperature oven at 120°C for drying for 12 h to obtain modified porous carbon.
[0060] Example 3
[0061] It is basically the same as Example 2, except that in step S2, the multi-element alloy powder, diamond, modified porous carbon, and binder are mixed in a mass ratio of 100:4:1:1.
[0062] Comparative Example 1
[0063] It is basically the same as Example 2, except that in step S2, the multi-element alloy powder, diamond, modified porous carbon, and binder are mixed in a mass ratio of 100:4:1.2:1.
[0064] Comparative Example 2
[0065] The method is basically the same as Example 2, except that: the preparation method of the modified porous carbon is:
[0066] T1. Place zinc citrate in a tubular furnace in a nitrogen atmosphere, heat it to 700°C at a heating rate of 3°C / min and keep it warm for 2 hours. After the heating is completed, cool it naturally and collect it to obtain a black solid. Immerse the black solid in 2 mol / L hydrochloric acid to remove inorganic impurities, wash it with water and ethanol three times each, filter it, and transfer it to a 120°C constant temperature oven to dry it for 12 hours to obtain porous carbon;
[0067] T2. Porous carbon, dopamine hydrochloride and 60 wt% ethanol aqueous solution were stirred and mixed at a mass ratio of 3:1:75 at 500 rpm for 5 min, and then 0.3 times the mass of intercalated porous carbon was added with ammonium molybdate tetrahydrate, and then the pH was adjusted to 9.3 with 10 wt% ammonia water, and stirring was maintained. The reaction was continued for 12 h. After the reaction was completed, the mixture was washed with water and ethanol three times each, filtered and transferred to a constant temperature oven at 120°C for drying for 12 h to obtain modified porous carbon.
[0068] Comparative Example 3
[0069] The method is basically the same as Example 2, except that: the preparation method of the modified porous carbon is:
[0070] T1. Place zinc citrate in a tubular furnace in a nitrogen atmosphere, heat it to 700°C at a heating rate of 3°C / min and keep it warm for 2 hours. After the heating is completed, cool it naturally and collect it to obtain a black solid. Immerse the black solid in 2 mol / L hydrochloric acid to remove inorganic impurities, wash it with water and ethanol three times each, filter it, and transfer it to a 120°C constant temperature oven to dry it for 12 hours to obtain porous carbon;
[0071] T2. The porous carbon, octylamine and 60 wt% ethanol aqueous solution were stirred and mixed at a mass ratio of 3:1:25 at a rotation speed of 350 rpm, and then ultrasonicated for 5 h at an ultrasonic power of 150 W and a frequency of 30 kHz. The mixture was washed three times with water and ethanol respectively, filtered and transferred to a constant temperature oven at 120°C for drying for 12 h to obtain modified porous carbon.
[0072] Comparative Example 4
[0073] The method is substantially the same as Example 2, except that the modified porous carbon is replaced by porous carbon;
[0074] The preparation method of porous carbon is as follows:
[0075] Zinc citrate was placed in a tubular furnace in a nitrogen atmosphere, and the temperature was increased to 700°C at a heating rate of 3°C / min and kept at this temperature for 2 hours. After the temperature was naturally cooled, a black solid was collected and immersed in 2 mol / L hydrochloric acid to remove inorganic impurities. The black solid was washed three times with water and ethanol respectively, then filtered and transferred to a constant temperature oven at 120°C for drying for 12 hours to obtain porous carbon.
[0076] Comparative Example 5
[0077] It is basically the same as Example 2, except that: no modified porous carbon is added.
[0078] It should be noted that the graphite mold used in the preparation of the composite material in the above-mentioned embodiments and comparative examples is selected according to different needs. For example, when it is made into a grinding tool, the shape is a circular ring. The prepared diamond composite material presents a grinding wheel with an outer diameter of 25 mm, a working thickness of 10 mm, and a working width of 20 mm, which is combined with a structurally matching aluminum wheel hub to form a grinding tool; when making samples for performance testing, a rectangular mold can be selected to make a 30 mm × 12 mm × 6 mm sample block.
[0079] Test Case
[0080] In order to study the influence of the bonding state of modified porous carbon with multi-component alloy and diamond in the embodiments and comparative examples, the diamond detachment pits at the fracture of the abrasive tools composed of the composite materials prepared in the embodiments and comparative examples and the diamond encapsulation state of the multi-component alloy at the fracture of the abrasive tool samples were observed. Figure 2 The encapsulation state of Comparative Example 4 is shown, and the matrix has a good grip on the diamond, indicating that the ratio of the multi-element alloy of the present invention has a good advantage; Figure 3 It can be seen that the modified porous carbon prepared in Example 1 is mainly dispersed on the diamond surface; Figure 4 It can be seen that the modified porous carbon prepared in Example 2 is dispersed on the diamond surface and effectively dispersed in the multi-element alloy matrix. Figure 5 It can be seen that the addition of excessive modified porous carbon in Comparative Example 1 will form agglomerates on the diamond surface and in the multi-element alloy matrix, and such a structure is not conducive to heat transfer; Figure 6 It can be seen that in comparative example 3 where no molybdenum is added, at the same addition ratio, the modified porous carbon is also prone to form agglomerates on the diamond surface and cannot be effectively dispersed in the multi-alloy matrix.
[0081] The diamond composite material samples prepared in the embodiment and the comparative example were subjected to hardness test, bending strength test and wear ratio test, wherein the Rockwell hardness was tested by HR-150A Rockwell hardness tester, and the average value was taken after 3 tests; the three-point bending test was performed on the sample using a universal testing machine, and the bending strength of the sample was tested, and the average value was taken after 3 tests; the brown corundum grinding wheel of 200mm×25mm×32mm was used for grinding, and the ratio of the loss mass of the grinding brown corundum grinding wheel to the loss mass of the test sample was taken (the larger the value, the better the wear resistance), the grinding wheel linear speed was 35m / s, the grinding pressure was 5N, the grinding time was 10min, and the average value was taken after 3 tests. These results are shown in Table 1.
[0082] Table 1 Mechanical properties and wear resistance test results
[0083] Rockwell hardness (HRB) Flexural strength(MPa) Wear ratio Example 1 103.5 338.3 186.7 Example 2 107.5 366.8 205.6 Example 3 105.3 357.9 199.8 Comparative Example 1 94.1 305.6 139.5 Comparative Example 2 102.3 326.5 147.5 Comparative Example 3 101.5 322.4 157.8 Comparative Example 4 92.1 299.2 125.3 Comparative Example 5 108.9 318.3 164.5
[0084] From the test results of Table 1, it can be seen that compared with Comparative Example 5 in which porous carbon and modified porous carbon are not added, the various properties of Comparative Example 4 in which porous carbon is directly added and Comparative Example 1 in which modified porous carbon is added more are significantly reduced. This is because the porous carbon prepared by calcining zinc citrate has a close interlayer spacing. Although it has a rich pore structure, it still cannot be well dispersed in the multi-element alloy or well dispersed on the diamond surface, and agglomerates in the structure, which reduces the mechanical properties of the material. A large amount of modified porous carbon will agglomerate in the multi-element alloy because its internal stress is uneven. Comparative Example 3 of modified porous carbon obtained only by intercalation treatment and Comparative Example 2 in which molybdenum-containing polydopamine is modified on the porous carbon surface without intercalation treatment, cannot effectively inhibit the decrease in hardness of carbon materials added to the multi-element alloy system. This is because after intercalation treatment and polydopamine modification of molybdenum, polydopamine polymerized molybdenum is reduced during the sintering process, which enhances the effect with multi-element alloy and diamond, thereby significantly improving the mechanical properties and wear resistance of the diamond composite material.
[0085] The thermal conductivity of the diamond composite material samples prepared in the embodiment and the comparative example was also measured using a laser thermal conductivity analyzer. The results are shown in Table 2.
[0086] Table 2 Thermal conductivity results
[0087] <![CDATA[Thermal conductivity (W·m -1 ·K -1 )]]> Example 1 57.56 Example 2 64.59 Example 3 61.97 Comparative Example 1 58.56 Comparative Example 2 53.14 Comparative Example 3 51.23 Comparative Example 4 48.66 Comparative Example 5 45.63
[0088] From the test results in Table 2, it can be seen that compared with Comparative Example 5, after adding porous carbon / modified porous carbon, the thermal conductivity numbers are improved. This is because porous carbon itself has good thermal conductivity. Compared with Example 3 and Comparative Example 1, Example 2 adds less modified porous carbon, but has a higher thermal conductivity coefficient. This is because the modified porous carbon is well dispersed on the surface of the multi-element alloy and diamond, forming a good thermal conductive network, which can dissipate heat more effectively.
[0089] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A super wear-resistant diamond composite material, characterized in that: It is obtained by mixing multi-element alloy, diamond, modified porous carbon and adhesive in a mass ratio of 90-100:3-5:0.5-1:0.5-2 and then sintering; Among them, the multi-element alloy is Fe 15~30 Co 10~15 Ni 10~15 Cu 30~50 W 2~5 Sn 5~10 .
2. The ultra-wear-resistant diamond composite material according to claim 1, characterized in that: The preparation method of the modified porous carbon comprises: The organic acid metal salt is placed in a protective atmosphere and calcined to obtain porous carbon; The porous carbon, aliphatic amine and ethanol aqueous solution are mixed and then subjected to ultrasonic treatment to obtain intercalated porous carbon; The intercalated porous carbon, dopamine hydrochloride and ethanol aqueous solution are mixed, the pH is adjusted, and then stirred for reaction to obtain modified porous carbon.
3. The ultra-wear-resistant diamond composite material according to claim 2, characterized in that: The mass ratio of the porous carbon, the fatty amine and the ethanol aqueous solution is 2-5:1-3:20-30; The ultrasonic treatment lasts for 3 to 8 hours at a power of 100 to 200 W and a frequency of 20 to 50 kHz; The mass ratio of the intercalated porous carbon, dopamine hydrochloride and ethanol aqueous solution is 2-5:1-3:60-80; Adjust pH to 8.5-9.
5.
4. The ultra-wear-resistant diamond composite material according to claim 2, characterized in that: After the intercalated porous carbon, dopamine hydrochloride and ethanol aqueous solution are stirred, a soluble molybdenum salt in an amount of 0.2 to 0.5 times the mass of the intercalated porous carbon is added.
5. The ultra-wear-resistant diamond composite material according to claim 2, characterized in that: The carbon number of the fatty amine is 4 to 20.
6. The ultra-wear-resistant diamond composite material according to claim 1, characterized in that: The particle size of the multi-component alloy is 50-200 μm.
7. The ultra-wear-resistant diamond composite material according to claim 1, characterized in that: The particle size of the diamond is 100-300 μm.
8. The super wear-resistant diamond composite material according to claim 1, characterized in that: The adhesive includes at least one of paraffin, polyvinyl alcohol and stearic acid.
9. A method for preparing the super wear-resistant diamond composite material according to any one of claims 1 to 8, characterized in that: include, The Fe powder, Co powder, Ni powder, Cu powder, W powder and Sn powder are mixed and sintered to obtain the multi-element alloy Fe 15~30 Co 10~15 Ni 10~ 15 Cu 30~50 W 2~5 Sn 5~10 ; The multi-element alloy, diamond, modified porous carbon and adhesive are mixed in a mass ratio of 90-100:3-5:0.5-1:0.5-2 and then sintered to obtain a super wear-resistant diamond composite material.
10. The method for preparing the super wear-resistant diamond composite material according to claim 9, characterized in that: The sintering is carried out by spark plasma sintering at a temperature of 800 to 1000° C. and a pressure of 20 to 30 MPa for 5 to 15 minutes.
Citation Information
Patent Citations
Fully-prealloyed powder and preparation method thereof
CN105463291A
Lanthanum-oxide-doped modified copper-based graphite motor carbon brush and preparation method thereof
CN106384924A
Metal based diamond composite tool bit and preparation method thereof and drill bit
CN108274004A
Novel multi-principal element alloy-diamond grinding tool material as well as preparation method and application thereof
CN114645171A
Polyurethane waterproof anticorrosive paint and preparation method thereof
CN118146710A